Determining the Performance of Sea Tolls in Indonesia : Analysis of Port Infrastructure, Logistics Connectivity, and Fleet Capacity: Management - Grace Vita Vidyani; Olfebri Olfebri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the influence of port infrastructure, logistics connectivity, and fleet capacity on the performance of sea tolls in Indonesia. The approach used in this literature review study is descriptive qualitative. The data collection technique used is a literature study or review of relevant previous articles published between 2021 and 2026. The technique used in this literature review is comparative analysis. The data used in this descriptive qualitative approach came from previous studies relevant to this study and sourced from academic online media such as Thomson Reuters Journal, Springer, Taylor & Francis, Scopus Q2-Q4 Emerald, Elsevier, Sage, Web of Science, Sinta 2-5 Journal, DOAJ, EBSCO, Google Scholar, Copernicus, and digital reference books. The results of the study show that: 1) Port infrastructure affects sea toll performance; 2) Logistics connectivity affects sea toll performance; 3) Fleet capacity affects sea toll performance.